2009
DOI: 10.1149/1.3106670
|View full text |Cite
|
Sign up to set email alerts
|

PL and EL Characteristics in New Blue Emitting La2O3:Bi Phosphor Thin Films

Abstract: The electroluminescent (EL) and photoluminescent (PL) characteristics in new blue emitting Bi-activated La 2 O 3 oxide phosphor thin films prepared using a conventional or a combinatorial r.f. magnetron sputtering deposition method followed by postannealing are investigated. Intense blue PL emission was observed from the prepared La 2 O 3 :Bi phosphor thin films. In addition, a high-luminance in blue EL emission was obtained in thin-film electroluminescent (TFEL) devices fabricated using the La 2 O 3 :Bi phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…All the Bi doped La 2 O 3 compounds show broad blue emission originating from transitions in Bi 3+ ion ( 3 P 1 → 1 S 0 ) and have almost the same emission maximum at 458 nm. Blue emission from Bi doped La 2 O 3 phosphor thin films has been previously reported . The emission intensity increases with increase in dopant (Bi) concentration from x=0.0025 to x=0.005.…”
Section: Optical Studiesmentioning
confidence: 77%
See 1 more Smart Citation
“…All the Bi doped La 2 O 3 compounds show broad blue emission originating from transitions in Bi 3+ ion ( 3 P 1 → 1 S 0 ) and have almost the same emission maximum at 458 nm. Blue emission from Bi doped La 2 O 3 phosphor thin films has been previously reported . The emission intensity increases with increase in dopant (Bi) concentration from x=0.0025 to x=0.005.…”
Section: Optical Studiesmentioning
confidence: 77%
“…Blue emission from Bi doped La 2 O 3 phosphor thin films has been previously reported. [45] The emission intensity increases with increase in dopant (Bi) concentration from x = 0.0025 to x = 0.005. Thereafter, it decreases gradually with further increase in the dopant concentration from x = 0.01 to x = 0.04.…”
Section: Photoluminescence (Pl)bi Doped La 2 O 3 Compounds (La 2-2x Bmentioning
confidence: 97%
“…For developing inorganic thin-film electroluminescent (TFEL) displays and/or lamps fabricated using oxide phosphor thin films, we must investigate chemically stable oxide phosphor thin films suitable for obtaining high-luminance multicolor emissions. Recently, we reported that intense blue-green PL and EL emissions were observed from binary oxide phosphor thin films using Ga 2 O 3 or La 2 O 3 as the host material (1,2). Luminescent characteristics in Ga 2 O 3 and La 2 O 3 phosphor thin films have also been reported using such a dopant as Mn, Cr, or a rare earth element as the activator (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 95%